Simbolismo ed escatologia nell’Apocalisse apocrifa di Giovanni: un confronto con l’Apocalisse canonica - Valeriani, Emanuela (Apocrypha, 2015)
This paper analyzes the Apocryphal Apocalypse of John - better known as the First Apocryphal Apocalypse of John - starting from the comparison with the canonical one with the aim of defining its social and cultural context that is still rather neglected among scholars together with its different textual forms. The investigation starts from the analysis of the literary genre, the symbolic language and the eschatological theology and immediately puts in evidence both, its predilection for the oracular dialogue, rather than visions, as a means of the divine revelation, and its theological position, based on the idea of a single universal resurrection, which introduces an antimillenarian eschatological representation. The absence of any reference to the Millennium, as it is represented in the canonical Apocalypse, and the absence of the devil, as one of the protagonists of the final events, are peculiar elements of this text in which the eschatological enemy is represented by the antichrist. The detailed description of its appearance occupies the central part of the narrative and combines typical elements of the portraits of the antichrist widely used in Christian apocalypses. Due to the lack of clear historical, political and social references within the narrative, the dating of this text is still an open question. Taking into account all the proposals put forward so far, it seems convincing to consider the viii century as the reliable period of composition, basically as a result of the use of a terminology which is not attested before the Iconoclasm, σεπτὴ εἰκών, but which is widely used during the controversy in defense of the veneration of the icons. Therefore, the presence of this expression must be considered as a fundamental element to identify the context of the origin of the Apocryphal Apocalypse of John, but only after establishing a new critical edition that takes into account the entire manuscript tradition, it will be possible to give a definitive contribution in this sense.